A new dimeric protoberberine alkaloid and other compounds from the tubers of Tinospora dentata. Issue 1 (2nd January 2021) - Lam, Sio-Hong; Jian, Shu-Duan; Hwang, Tsong-Long; Chen, Po-Jen; Hung, Hsin-Yi; Kuo, Ping-Chung; Wu, Tian-Shung
Abstract: A new dimeric quaternary protoberberine alkaloid, bispalmatrubine (1 ), and thirteen known compounds (2 -14 ) were purified from the tubers of Tinospora dentata . Their structures were determined by spectroscopic and spectrometric analytical methods. Among the isolates, eight compounds were examined for their in vitro anti-inflammatory potential and several tested alkaloids displayed moderate inhibitory effects of N -formyl-methionyl-leucyl-phenylalanine/cytochalasin B (fMLP/CB)-induced superoxide anion generation and elastase release. GRAPHICAL ABSTRACT: